Bíblia como livro literário - Nering, Gustavo (2013)
As a final result one has a visual system that can be applied to all volumes from the Bible. The Bible was divided because of its size and one of the goals of this paper is to bring the Bible as literary book, with a cleaner visual, more friendly and inviting to the reader. To get to this goal it was necessary to bring, in a brief way, a Bible history and to defend its literary character. After that one studied graphic projects from Bibles and literary books wich had given base to editorial decisions and helped on the book design decisions. Then the book was diagrammed and everything that was decided was tested in the manufacturing of the volume of the book of Genesis.